2010
DOI: 10.1111/j.1744-7909.2010.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

BYPASS1: How a Tiny Mutant Tells a Big Story about Root‐to‐shoot Signaling

Abstract: Plants coordinate their development using long-distance signaling. The vascular system provides a route for long-distance movement, and specifically the xylem for root-to-shoot signaling. Root-toshoot signals play roles communicating soil conditions, and these signals are important for agricultural water conservation. Using genetic approaches, the Arabidopsis bypass1 (bps1) mutant, which over-produces a root-derived signal, was identified. Although bps1 mutants have both root and shoot defects, the shoot can d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Field-grown mhz5 plants under environmental light conditions did not resemble wild-type plants, suggesting that light can only partially substitute for MHZ5/CRTISO activity, which is consistent with previous reports in Arabidopsis and tomato (Isaacson et al, 2002;Park et al, 2002). In addition to the current roles of the carotenoid-derived ABA pathway in the regulation of rice seedling growth, other carotenoid-derived molecules, e.g., SL, BYPASS, and uncharacterized compounds, may be responsible for tiller formation (Supplemental Figure 1), root development (Supplemental Figure 2), and other phenotypic changes in fieldgrown mhz5 plants (Nambara and Marion-Poll, 2005;Umehara et al, 2008;Sieburth and Lee, 2010;Kapulnik et al, 2011;Puig et al, 2012;Ramel et al, 2012;Van Norman et al, 2014).…”
Section: Ethylene Regulates Carotenoid Biosynthesis In Etiolated Ricesupporting
confidence: 79%
See 1 more Smart Citation
“…Field-grown mhz5 plants under environmental light conditions did not resemble wild-type plants, suggesting that light can only partially substitute for MHZ5/CRTISO activity, which is consistent with previous reports in Arabidopsis and tomato (Isaacson et al, 2002;Park et al, 2002). In addition to the current roles of the carotenoid-derived ABA pathway in the regulation of rice seedling growth, other carotenoid-derived molecules, e.g., SL, BYPASS, and uncharacterized compounds, may be responsible for tiller formation (Supplemental Figure 1), root development (Supplemental Figure 2), and other phenotypic changes in fieldgrown mhz5 plants (Nambara and Marion-Poll, 2005;Umehara et al, 2008;Sieburth and Lee, 2010;Kapulnik et al, 2011;Puig et al, 2012;Ramel et al, 2012;Van Norman et al, 2014).…”
Section: Ethylene Regulates Carotenoid Biosynthesis In Etiolated Ricesupporting
confidence: 79%
“…Carotenoid-derived compounds, such as SL, ABA, BYPASS, b-cyclocitral, and other uncharacterized molecules, modulate plant developmental processes and stress responses in many organs (Xie et al, 2010;Sieburth and Lee, 2010;Walter et al, 2010;Cazzonelli and Pogson, 2010;Puig et al, 2012;Ramel et al, 2012;Avendaño-Vázquez et al, 2014;Van Norman et al, 2014;Liu et al, 2015). The regulation of carotenoid biosynthesis is interconnected with plant developmental and environmental responses, and the biosynthesis pathway is regulated at both the transcriptional and posttranscriptional levels in plants ( Ruiz-Sola and Rodríguez-Concepción, 2012).…”
Section: Ethylene Regulates Carotenoid Biosynthesis In Etiolated Ricementioning
confidence: 99%
“…The plant organs to detect drought stress conditions are roots, and upon drought perception, they release signals to induce resistance and/or adapt their architecture for optimal growth under these conditions (Sieburth and Lee, 2010;Atkinson and Urwin, 2012). Split-root experiments in drought conditions and drought-inducible maize (Zea mays) root signals indicate that roots generate uncharacterized droughtinducible signals that move to the aerial parts of the plant and confer drought resistance to the shoots (Went, 1943;Passioura, 1988;Saab and Sharp, 1989;Gowing et al, 1990;Chazen and Neumann, 1994).…”
mentioning
confidence: 99%
“…The pioneering studies of Fritz Went (1943) revealed the involvement of root‐derived signals that appeared to regulate growth of the vegetative regions of the plant. The roles of these signals in water use efficiency, control over shoot branching and overall shoot growth are reviewed in this Special Issue by Sieburth and Lee (2010). The identification of a novel protein, BYPASS1, is discussed with respect to its function in interdicting the synthesis of a novel root‐to‐shoot signal; this molecule may well be a branch product of the carotenoid biosynthetic pathway.…”
Section: Root‐to‐shoot Signaling Systems Control Physiological and Dementioning
confidence: 99%